PROBLEMS OF COMPLICATED INTRA-ABDOMINAL INFECTION’S ANTIBACTERIAL TREATMENT IN MULTIDISCIPLINARY HOSPITALS - Yu. M. Gomon; A. S. Kolbin; Yu. E. Balykina; M. A. Arepyeva; S. V. Sidorenko; V. V. Strizheletskiy; I. G. Ivanov; Yu. V. Lobzin; О. A. Grinenko (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2017)
The objective is to assess the economic efficiency of the current practice of complicated IAI (intra-abdominal infections) treatment with antibiotics compared to the strategy of the therapy with carbapenem without antipseudomonal activity (Ertapanem).Materials and methods. We analyzed the economic efficiency of the current practice of IAI treatment compared to alternative therapy.Results. In current practice the cost of treatment of 1 case of complicated IAI is 82771.85 rub compared to 91471.55 rub for alternative strategy. Analysis of the impact on the Russian budget, out of the expected number of IAI cases in the Russian Federation, revealed that the current practice of antibacterial therapy allows saving up to 544166014 rubles. The proceeds allows to treat additionally 6574 patients with IAI.Conclusions. In real practice the use of antibiotics in complicated IAI treatment was assessed as more beneficial. Nevertheless, there is a lack of necessary data regarding the bacterial resistance in dynamic that could provide more information about the real economic consequences of «collateral damage» due to the current practice of using the antibiotic therapy.